Laparoscopic management of a large extragonadal teratoma - Akmal Zulayla Mohd Zahid; Noorneza Abdul Rahman; Zeti Rahayu Karim; Effat Omar (Wolters Kluwer Medknow Publications, 2022)
Extragonadal teratoma of the omentum is a rare clinical entity. We report a case of a large omental teratoma in a postmenopausal woman who presented with 3 days history of right groin pain. She was previously diagnosed with right ovarian teratoma in 2013 but declined surgical intervention. Laparoscopy performed for suspected ovarian cyst torsion discovered a large omental teratoma measuring approximately 11 cm × 9 cm with the concurrent absence of the right fallopian tube and ovary. The mass was removed successfully via laparoscopic approach. The likely mechanism in this case is autoamputation of the adnexae due to chronic ovarian torsion. Establishing correct diagnosis preoperatively is difficult, however an extragonadal teratoma should be one of the differential diagnoses when a round, mobile mass is found in the abdomen. Laparoscopic management is feasible even in the presence of a large extragonadal teratoma.